A sequence of vectors in the x y plane is described by the recurrence equation,
p k + 1 = p k + v k
and
v k + 1 = ϕ 1 R v k
with p 0 = ( 0 , 0 ) and v 0 = ( 1 , 1 ) , and R is the following rotation matrix,
R = [ cos 2 π − sin 2 π sin 2 π cos 2 π ] = [ 0 − 1 1 0 ]
and ϕ is the golden ratio, ϕ = 2 1 + 5
If k → ∞ lim p k = ( a , b ) , then find a + 3 b
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Using complex numbers you find that:
p0 = 0
p1 = 1+i
p2 = (1+i) + i/phi (1+i)
p3 = (1+i) + i/phi (1+i) + (i/phi)² (1+i)
pn = (1+i) (1 + i/phi + (i/phi)² +...+ (i/phi)^(n-1))
Which is easy to solve in the limit. Only then a and b are switched, so in that sense the result is not quite the same. It is probably due to the fact that your rotation is clockwise and i rotates counter clockwise. So basically, that's what I got wrong.
Note to the author:
Generally rotation matrices are written like that:
R ( θ ) = [ cos ( θ ) sin ( θ ) − sin ( θ ) cos ( θ ) ]
Indeed your matrix is R ( − 2 π ) but the angle you used is 2 π .
My solution:
Let w n = R n v 0 = ϕ n v n .
Using that fact that R = R ( − 2 π ) we see that:
w 4 n = ( 1 , 1 ) w 4 n + 1 = ( 1 , − 1 ) w 4 n + 2 = ( − 1 , − 1 ) w 4 n + 3 = ( − 1 , 1 ) .
With the relation defining ( p n ) we have:
n → + ∞ lim p n = p = ( a , b ) = n = 0 ∑ + ∞ ϕ n 1 w n
Therefore:
a = n = 0 ∑ + ∞ ϕ 4 n 1 + n = 0 ∑ + ∞ ϕ 4 n + 1 1 − n = 0 ∑ + ∞ ϕ 4 n + 2 1 − n = 0 ∑ + ∞ ϕ 4 n + 2 1 and, b = n = 0 ∑ + ∞ ϕ 4 n 1 − n = 0 ∑ + ∞ ϕ 4 n + 1 1 − n = 0 ∑ + ∞ ϕ 4 n + 2 1 + n = 0 ∑ + ∞ ϕ 4 n + 2 1
Using the fact that for all integers k = 0 , m , if ∣ x ∣ < 1 then
n = 0 ∑ + ∞ x k n + m = x m n = 0 ∑ + ∞ ( x k ) n = 1 − x k x m
We get,
a = 1 − ϕ − 4 1 + ϕ − 1 − ϕ − 2 − ϕ − 3 = ϕ 4 − 1 ϕ 4 + ϕ 3 − ϕ 2 − ϕ and, b = 1 − ϕ − 4 1 − ϕ − 1 − ϕ − 2 + ϕ − 3 = ϕ 4 − 1 ϕ 4 − ϕ 3 − ϕ 2 + ϕ
Hence,
a + 3 b = ϕ 4 − 1 4 ϕ 4 − 2 ϕ 3 − 4 ϕ 2 + 2 ϕ
Using the fact that ϕ 2 = ϕ + 1 and so ϕ 3 = 2 ϕ + 1 as well as ϕ 4 = 3 ϕ + 2
a + 3 b = 3 ϕ + 1 1 2 ϕ + 8 − 4 ϕ − 2 − 4 ϕ − 4 + 2 ϕ = 3 ϕ + 1 6 ϕ + 2 = 2
R 2 = − I ⇒ ( ϕ 1 R ) 2 = − ϕ 2 1 I ⇒ v 2 k = ( − ϕ 2 1 ) k v 0 and v 2 k + 1 = ( − ϕ 2 1 ) k v 1 ⇒ v 2 k + v 2 k + 1 = ( − ϕ 2 1 ) k ( v 0 + v 1 )
p 2 n + 1 = ∑ k = 0 n v k + ∑ k = 0 n v k + 1
Now using the fact that for ∣ r ∣ < 1 , we can write 1 + r + r 2 + . . . = 1 − r 1 , and putting r = − ϕ 2 1
lim n → ∞ p 2 n + 1 = 1 + ϕ 2 1 1 ( v 0 , v 1 ) = 1 + ϕ 2 1 1 ( 1 + ϕ 1 , 1 − ϕ 1 )
lim n → ∞ p 2 n + 1 = 5 + 5 5 + 3 ( 5 + 1 5 + 3 , 5 + 1 5 − 1 ) = ( 3 5 + 5 3 5 + 7 , 3 5 + 5 5 + 1 )
a + 3 b = 3 5 + 5 6 5 + 1 0 = 2
Similarly, prove that lim n → ∞ p 2 n converges to the same value so that the given limit exists.
For the last step, remarking that p 2 n + 1 − p 2 n = v 2 n n → + ∞ ⟶ 0 is enough to prove that ( p 2 n ) converges to the same limit as ( p 2 n + 1 ) which we know to be convergent. It is true because R is orthogonal and ∣ 1 / ϕ ∣ < 1 , therefore v n = ϕ n 1 R n v 0 n → + ∞ ⟶ 0 .
Problem Loading...
Note Loading...
Set Loading...
define K = ϕ 1 R . then [ p n + 1 v n + 1 ] = [ I 0 I K ] [ p n v n ] if we let A = [ I 0 I K ] , then the nth term in the sequence is [ p n v n ] = A n [ p 0 v 0 ]
lemma : A n = [ I 0 I + K + K 2 + . . . + K n − 1 K n ] proof (by induction): the base case with n=1 is true. we have A n + 1 = A n A = [ I 0 I + K + K 2 + . . . + K n − 1 K n ] [ I 0 I K ] = [ I 0 I + K + K 2 + . . . + K n − 1 + K n K n + 1 ] hence proved.
note lim n → ∞ K n = 0 . Using this we have [ p ∞ v ∞ ] = [ I 0 I + K + K 2 + . . . 0 ] [ p 0 v 0 ] → p ∞ = p 0 + ( I + K + K 2 + . . . ) v 0 notice that R n is periodic, as 4 90 degree rotation is the same as not rotating(i.e identity matrix). infact the powers of n starting at n=1 goes R , − I , − R , I , R . . . . plugging this in we have p ∞ = p 0 + ( I + ϕ 1 R − ϕ 2 1 I − ϕ 3 1 R + ϕ 4 1 I + . . . . . ) v 0 = p 0 + 1 + ϕ 2 1 1 ( I + ϕ R ) v 0 note that geometric series was used. the rest is just plugging in, giving the vector 1 + ϕ 2 1 1 ⎣ ⎢ ⎡ 1 + ϕ 1 1 − ϕ 1 ⎦ ⎥ ⎤